THE PROGRAMS FOR THE “THIRD AGE” AND THE CONSTRUCTION OF A NEW SIGNIFICANCE OF WHAT IS OLD AGE (Fiep Bulletin - online, 2013)
With the present study we have as a goal to investigate the meaning of “be old” among women that participate from the third age groups. Treats an empiric research, not systematized. The investigation instrument was the observation and the key question “what you are? " toward the denial: “I am not old”. The data were collected in different sceneries, proportionated for our position of educational. We organized the information in two analysis categories: to be old in the view of the women in an long permanence intitution and to be old in the view of tehe women that participate in the convivence groups. The analysis showed that in the long permanence intitution the age is in the other, in other words, in the man and in the woman that the " me " don't want to be. In the convivence groups the age is categorically denied and stealed in the women images that are in the phase of the climacteric. The social representations are anchored in the image of the " me " that want to be: in that woman that dances, that imitates Carmem Miranda and that speaks about sex. Toward the sentence " I am not old " we only obtained two answers: “I am young” and "I don't know...I just know that I am not old". We conclued inferring that the programs in question in on side are in favor to an active old age, but in the other side, they not developed in the overthrow of the same.
Keywords: Age; group of the third age; social representations